A brief guide to the science and art of writing manuscripts in biomedicine - Diego A. Forero (Journal of Translational Medicine, 2020)
Abstract Publishing articles in international scientific journals is the primary method for the communication of validated research findings and ideas. Journal articles are commonly used as a major input for evaluations of researchers and institutions. Few articles have been published previously about the different aspects needed for writing high-quality articles. In this manuscript, we provide an updated and brief guide for the multiple dimensions needed for writing manuscripts in the health and biological sciences, from current, international and interdisciplinary perspectives and from our expertise as authors, peer reviewers and editors. We provide key suggestions for writing major sections of the manuscript (e.g. title, abstract, introduction, methods, results and discussion), for submitting the manuscript and bring an overview of the peer review process and  of the post-publication impact of the articles.